PEMAHAMAN DAN PENANGANAN DISLEKSIA PADA PESERTA DIDIK SEKOLAH DASAR DI MIN 1 PONTIANAK: TINJAUAN LITERATUR - Afrilya Herianty; Ngatmini Ngatmini (STKIP Subang, 2024)
In the learning process at school there are several obstacles, including some students showing symptoms of not being able to achieve the expected learning outcomes. The problem of learning disorders is often found, one of which is difficulty reading and writing. In fact, one of the learning successes of students in participating in learning activities is determined by their ability to read and write, for this reason teachers must have an understanding and handling of students' dyslexia. The aim of this research is to increase understanding of the characteristics and symptoms of dyslexia in students at MIN 1 Pontianak. The techniques used are interviews, observation and data documentation. The treatments used are general treatment and specific treatment.